9 Routine non-invasive vs invasive management in patients with prior CABG with a NSTE-ACS: a randomised controlled trial. (25th January 2018) - Lee, Matthew MY; Petrie, Mark C; Rocchiccioli, Paul; Simpson, Joanne; Jackson, Colette; Brown, Ammani; Corcoran, David; Mangion, Kenneth; Cialdella, Pio; Sidik, Novalia; McEntegart, Margaret; Shaukat, Aadil; et al.
Abstract : Background: There is an evidence-gap about how to best treat patients with a history of prior CABG presenting with a NSTE-ACS because these patients were excluded from key randomised trials. Methods: The CABG-ACS pilot trial (NCT01895751 ) randomised patients with a NSTE-ACS and prior CABG to routine invasive or non-invasive management. The primary efficacy outcome was a composite of all-cause death, rehospitalisation for refractory ischaemia/angina, MI and HF hospitalisation. The primary safety outcome was a composite of bleeding, stroke, procedure-related MI and worsening renal function. A CEC assessed events. Results: 60 patients (mean ±SD age 71±9 years, 28% female) were randomised to invasive (n=31) or non-invasive (n=29) management. The invasive group had worse NYHA class (p=0.044) and less valve disease (17% vs 27%; p=0.035). Other comorbidities, age, sex, CCS grade, frailty score and medications were similar. Baseline LIMA grafts were similar (p=0.720). All invasive group patients had invasive management (mean BCIS-1 Jeopardy Score 7±4) and 6 (19%) had PCI. 6 non-invasive group patients ended up having invasive management and 3 (50%) had PCI. No patients had redo CABG. The primary efficacy outcome occurred in 42% invasive vs 45% non-invasive groups (RR (95% CI) 0.94 (0.52, 1.67); p=1.000). The primary safety outcome occurred in 26% invasive vs 31% non-invasive groups (RR 0.83 (0.37, 1.86); p=0.777). EQ-5D was similar at 1 year. Conclusion: Compared with routine non-invasive management, a strategy of routine invasive management was not associated with patient benefits.